Translation, modernity, acceptability—from language reform to cultural resistance in translation practice in China - Yuan, Mingming (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper compares the linguistic acceptability in the Chinese translations of Peter Pan from a diachronic perspective, in terms of how changing socio-cultural factors over different time periods influence the linguistic acceptability of the target text. Linguistic acceptability is defined in relation to the extent to which translation conforms to dominant conventions and expectations in the target language. Relating to the polysystem theory, the paper first analyses the different roles translated literature has played in the Chinese literary system from the 1920s to the present, highlighting how, as translated literature moves from a central to a peripheral position, the preferred method of translation changes from innovative methods compromising the acceptability of the target text to conservative methods prioritising high acceptability. As part of the target literature polysystem, translation practice inevitably bears the mark of history. Three translations of J. M. Barrie’s Peter Pan, completed respectively in 1929 (Liang’s), 1991 (Yang’s) and 2011 (Ren’s) are compared in terms of their linguistic acceptability, illustrating how the changed position of translated literature results in the change of preferred translating methods, signalling a move from language reform to cultural resistance in the prevalent translation norms in China.